An aqueous organic iron-based flow battery and methods of making the same

CN122992121APending Publication Date: 2026-10-27CHANGSHA UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611411044.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-11
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0006]本发明实施例的目的在于提供一种水系有机铁基液流电池及其制备方法,以实现解决邻二氮杂菲类材料应用于液流电池时存在的稳定性差、溶解度有限及电化学性能不足的问题,提升电池长期循环稳定性与储能性能

Benefits of technology

[0016]与现有正极电解液制备技术相比,本发明的有益效果包括:本发明采用“一锅法”原位制备液流电池用pH中性有机亚铁电解液,制备方法简单便捷,无需额外的分离提纯操作,为液流电池关键材料的开发提供了全新的思路和方向;从配位稳定性能来看,1,10-二氮杂菲和本发明添加剂与二价亚铁离子在pH中性条件下形成配合物的稳定常数分别为21.3和14.3,表明二价亚铁离子与1,10-二氮杂菲在溶液中的配位更稳定,因此本发明添加剂不会影响电解液的氧化电位,而1,10-二氮杂菲和本发明添加剂与三价铁离子在pH中性条件下形成配合物的稳定常数分别为14.1和25.1,说明本发明添加剂能够有效稳定三价铁离子,进而降低电解液在放电过程中电解质的析出,显著提高正极电活性物质的稳定性;同时,本发明所用原料储量丰富、成本低廉,且制备过程不涉及复杂操作,具备设备成本低、操作方便、流程简单等优势,不仅为电解液的规模化制备奠定了基础,还具有广阔的应用前景,有助于推动液流电池技术的进一步发展,本发明在不影响电解液氧化电位的前提下提高正极电活性物质稳定性的核心目标。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122992121A_ABST
    Figure CN122992121A_ABST
Patent Text Reader

Abstract

The application discloses a kind of aqueous organic iron-based flow battery and preparation method thereof, it is related to flow battery technical field.The preparation method is first prepared neutral salt solution, anion exchange membrane is washed, soaked ionization and washing standby treatment, then with ferrous sulfate and ortho-diazaphen as raw material preparation positive electrode electric active substance, after EDTA chelation, positive electrode electrolyte is obtained;Violets derivative is selected and dissolved in neutral salt solution, after oxygen removal, negative electrode electrolyte is prepared, finally with graphite felt or carbon felt as electrode, aqueous organic iron-based redox flow battery is assembled.The application avoids the problems such as membrane structure damage, ion conduction obstruction and frequent side reactions caused by improper activator and process parameters by optimizing the activation of diaphragm, electrolyte preparation and battery assembly process, effectively improves the ion conduction performance, chemical stability and energy density of the battery, and the process is controllable.The battery prepared has excellent ion selectivity and operating stability, and is suitable for large-scale application requirements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of flow battery technology, and in particular relates to an aqueous organic iron-based flow battery and its preparation method. Background Technology

[0002] With the increasing depletion of fossil fuels, the environmental problems they cause are becoming increasingly prominent. Therefore, developing new energy power systems has crucial practical significance and value. Currently, wind power and solar power are the most widely used new energy power generation technologies. However, wind and solar energy have significant time-sensitivity, resulting in inherent defects such as discontinuous power generation and unstable power output. There is an urgent need to equip them with corresponding power storage and conversion devices to ensure the stable operation of the power system. Among numerous electrochemical energy storage technologies, redox flow batteries, with their unique "split" battery structure, possess core advantages such as flexible design, long cycle life, and excellent safety performance, and have become one of the most promising large-scale energy storage technologies.

[0003] Aqueous organic redox flow batteries are a novel type of flow battery technology. The organic electroactive molecules they utilize are primarily composed of elements such as C, H, N, and O, which are abundant on Earth and possess significant advantages in terms of resource renewability. Simultaneously, the organic molecules can be precisely structurally designed according to actual application requirements, and by introducing functional groups with different properties, the solubility, stability, and redox potential of the organic electroactive molecules can be comprehensively controlled. However, they still face many challenges in practical applications. On the one hand, the preparation process of electroactive materials in organic systems is usually quite complex and cumbersome. On the other hand, organic molecules are prone to various unknown types of side reactions during actual battery operation, leading to degradation of the active molecules. 1,10-phenanthroline, as a typical organic ligand compound, possesses a bidentate ligand structure and can form stable complexes with various transition metals, showing potential application value in the field of active materials for organic flow battery electrolytes.

[0004] Currently, the application of o-phenanthroline materials in flow batteries still faces three major technological bottlenecks: First, stability issues. O-phenanthroline materials are prone to degradation, and their high-valence ions have an oxidative corrosive effect on electrode materials, leading to insufficient battery stability and rapid capacity decay during long-term cycling. Second, solubility limitations. The solubility of o-phenanthroline materials in aqueous solutions is at a moderate level, making it difficult to achieve high-concentration dissolution, which restricts the improvement of battery energy storage performance. Third, insufficient electrochemical performance. Compared with viologen, quinone, and nitroxide radical electroactive materials, the overall electrochemical performance of o-phenanthroline materials is significantly inferior, with their energy density being lower than that of viologen materials (which can reach an energy density of 19.0 Wh·L). -1Its stability is inferior to that of quinone materials (quinone materials typically have an energy density greater than 50 Wh·L). -1 Its electrochemical activity is relatively weaker than that of nitrile radical materials.

[0005] Furthermore, in the field of electroactive materials for flow batteries, there is a significant imbalance in the development of existing technologies. There is relatively more research on negative electrode electroactive materials and the technology is more mature, while the development of positive electrode electroactive materials is relatively lagging behind. Therefore, developing more high-performance positive electrode electrochemical active molecules has become a key technical challenge that urgently needs to be overcome to promote the development of aqueous organic redox flow battery technology. Summary of the Invention

[0006] The purpose of this invention is to provide an aqueous organic iron-based flow battery and its preparation method, so as to solve the problems of poor stability, limited solubility and insufficient electrochemical performance of o-phenanthroline materials when applied to flow batteries, and improve the long-term cycle stability and energy storage performance of the battery.

[0007] To solve the above-mentioned technical problems, the technical solution adopted by the present invention is a method for preparing an aqueous organic iron-based flow battery, comprising the following steps: S1. Prepare a neutral salt solution using deionized water; S2. The anion exchange membrane is cleaned to obtain a pretreated membrane. S3. The pretreated diaphragm is immersed in the neutral salt solution for ionization treatment; S4. Clean the ionized membrane and then soak it in deionized water for later use. S5. Ferrous sulfate and o-phenanthroline are dissolved in the neutral salt solution and stirred to obtain a positive electrode active material containing ferrous-o-phenanthroline complex; S6. EDTA is chelated with the positive electrode active material to prepare a positive electrode electrolyte. S7. Dissolve viologen derivatives in a neutral salt solution, stir to dissolve, and then perform deoxygenation treatment to obtain a negative electrode electrolyte. S8. Using graphite felt or carbon felt as electrode materials, the cleaned separator, positive electrolyte, and negative electrolyte are assembled to obtain an aqueous organic iron-based redox flow battery.

[0008] Furthermore, in step S1, the neutral salt solution is an aqueous solution of NaCl, NaBr, KCl, NH4Cl, or NH4Br, with a molar concentration of 0.1~2M; In step S2, the anion exchange membrane is cleaned by immersion in deionized water for 3-5 minutes.

[0009] Furthermore, in step S3, the duration of the immersion ionization treatment is 1 to 48 hours.

[0010] Furthermore, in step S4, the ionized membrane is washed 4 to 6 times with deionized water and then soaked in deionized water for later use.

[0011] Furthermore, in step S5, the molar concentration of the ferrous-o-phenanthroline complex is 0.1~0.5M, and the stirring time is 2h.

[0012] Furthermore, in step S6, the molar concentration ratio of EDTA to o-phenanthroline is 1:1 to 1:3.

[0013] Furthermore, in step S7, the viologen derivative is any one of MV, Dex-Vi, [(Me)(NPr)V]Cl3, [(NPr)2V]Br4, [(NPr)2TTz]Cl4, [(NPr)2PV]·4Cl, and [PyrPV]Cl4, with a molar concentration of 0.1~1M; The neutral salt solution used to prepare the negative electrode electrolyte has the same concentration as the neutral salt solution used to prepare the positive electrode electrolyte. The deoxygenation treatment is performed by introducing argon gas into a glove box for 40-50 minutes.

[0014] Furthermore, in step S8, the thickness of the graphite felt or carbon felt is 3~8mm.

[0015] An aqueous organic iron-based flow battery is prepared using the above-described method for preparing an aqueous organic iron-based flow battery.

[0016] Compared with existing cathode electrolyte preparation technologies, the beneficial effects of this invention include: This invention employs a "one-pot" in-situ preparation method for pH-neutral organic ferrous electrolytes used in flow batteries. The preparation method is simple and convenient, requiring no additional separation and purification operations, providing a novel approach and direction for the development of key materials for flow batteries. From the perspective of coordination stability, the stability constants of the complexes formed by 1,10-diaphenanthrene and the additive of this invention with divalent ferrous ions under pH-neutral conditions are 21.3 and 14.3, respectively, indicating that the coordination between divalent ferrous ions and 1,10-diaphenanthrene in solution is more stable. Therefore, the additive of this invention will not affect the oxidation potential of the electrolyte, while the 1,10-diaphenanthrene and the additive of this invention... The stability constants of the complexes formed by the additive and ferric ions under neutral pH conditions are 14.1 and 25.1, respectively, indicating that the additive of the present invention can effectively stabilize ferric ions, thereby reducing electrolyte deposition during discharge and significantly improving the stability of the positive electrode active material. Meanwhile, the raw materials used in this invention are abundant and inexpensive, and the preparation process does not involve complex operations, possessing advantages such as low equipment cost, convenient operation, and simple process. This not only lays the foundation for the large-scale preparation of electrolytes but also has broad application prospects, contributing to the further development of flow battery technology. The core objective of this invention is to improve the stability of the positive electrode active material without affecting the oxidation potential of the electrolyte. Attached Figure Description

[0017] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0018] Figure 1 Cyclic voltammetry curves of 1,1-diazanphenanthroline ferric chloride in sodium chloride aqueous solution; Figure 2 It has a molar concentration of 0.1 mol / L. -1 1,2-diazoxide ferrous sulfate and 0.2 mol / L -1 A flow single cell with methyl viologen and 1M NaCl as the supporting electrolyte at 20 mA / cm² -2 Cyclic efficiency diagram at current density; Figure 3 It has a molar concentration of 0.1 mol / L. -1 0.15 mol L of 1-diazoxide-phenanthroline iron -1 A flow single cell with methyl viologen and 1M NaCl as the supporting electrolyte at 20 mA / cm² -2 Cyclic efficiency diagram at current density; Figure 4It has a molar concentration of 0.1 mol / L. -1 1,2-diazoxide ferrous sulfate and 0.2 mol / L -1 A Dex-Vi, 1M NaCl-supported electrolyte flow single cell at 20 mA / cm² -2 Cyclic efficiency diagram at current density; Figure 5 It has a molar concentration of 0.1 mol / L. -1 0.15 mol L of 1-diazoxide-phenanthroline iron -1 A Dex-Vi, 1M NaCl-supported electrolyte flow single cell at 20 mA / cm² -2 Cyclic efficiency diagram at current density; Figure 6 It has a molar concentration of 0.1 mol / L. -1 1,2-diazoxide ferrous sulfate and 0.2 mol / L -1 A flow-through single cell with [(Me)(NPr)V]Cl3 and 1MNaCl as the supporting electrolyte operates at 20 mA / cm². -2 Cyclic efficiency diagram at current density; Figure 7 The molar concentration is 0.05 mol / L. -1 1,1-diazoxide ferric iron with 0.1 mol / L -1 A flow single cell with methyl viologen and 1M NaCl as the supporting electrolyte at 20 mA / cm² -2 Cyclic efficiency diagram at current density; Figure 8 It has a molar concentration of 0.1 mol / L. -1 1,2-diazoxide ferrous sulfate and 0.2 mol / L -1 A flow single cell with methyl viologen and 1M NaBr as the supporting electrolyte at 20 mA / cm² -2 Cyclic efficiency diagram at current density; Figure 9 It has a molar concentration of 0.1 mol / L. -1 1,2-diazoxide ferrous sulfate and 0.2 mol / L -1 A flow single cell with methyl viologen and 1 MKCl supporting electrolyte at 20 mA / cm² -2 Cyclic efficiency diagram at current density; Figure 10 It has a molar concentration of 0.2 mol / L. -1 1,4-diazoxide ferric iron with 0.3 mol / L -1 A Dex-Vi, 1M NaCl-supported electrolyte flow single cell at 20 mA / cm² -2 Cyclic efficiency diagram at current density; Figure 11 It has a molar concentration of 0.1 mol / L. -11,2-diazoxide ferrous sulfate and 0.2 mol / L -1 A flow single cell with methyl viologen and 2M NaCl as the supporting electrolyte at 20 mA / cm² -2 Cyclic efficiency diagram at current density; Figure 12 It has a molar concentration of 0.1 mol / L. -1 0.15 mol L of 1-diazoxide-phenanthroline iron -1 A flow single cell with methyl viologen and 1M NaCl as the supporting electrolyte at 20 mA / cm² -2 Cycle efficiency diagram of diaphragm without EDTA and pretreated with pure water at current density; Figure 13 This is a comparison chart of coulombic efficiency and energy efficiency data between Comparative Example 1 and Example 2; Figure 14 It has a molar concentration of 0.1 mol / L. -1 0.15 mol L of 1-diazoxide-phenanthroline iron -1 A flow single cell with methyl viologen and 1M NaCl as the supporting electrolyte at 20 mA / cm² -2 Cyclic efficiency of the membrane pretreated with 2M NaCl solution at current density; Figure 15 This is a comparison chart of coulombic efficiency and energy efficiency data between Comparative Example 2 and Example 2; Figure 16 It has a molar concentration of 0.1 mol / L. -1 0.15 mol L of 1-diazoxide-phenanthroline iron -1 A flow single cell with methyl viologen and 1M NaCl as the supporting electrolyte at 20 mA / cm² -2 Cyclic efficiency diagram of membrane pretreated with 0.1M NaCl solution at current density; Figure 17 This is a comparison chart of coulombic efficiency and energy efficiency data between Comparative Example 3 and Example 2; Figure 18 It has a molar concentration of 0.1 mol / L. -1 0.15 mol L of 1-diazoxide-phenanthroline iron -1 A flow single cell with methyl viologen and 1M NaCl as the supporting electrolyte at 20 mA / cm² -2 Cycle efficiency diagram of diaphragms pretreated with a soaking time of up to 48 hours at current density; Figure 19 This is a comparison chart of coulombic efficiency and energy efficiency data between Comparative Example 4 and Example 2; Figure 20 It has a molar concentration of 0.1 mol / L. -1 0.15 mol L of 1-diazoxide-phenanthroline iron -1A flow single cell with methyl viologen and 1M NaCl as the supporting electrolyte at 20 mA / cm² -2 Cycle efficiency diagram of removing S6EDTA chelation preparation step at current density; Figure 21 This is a comparison chart of coulombic efficiency and energy efficiency data between Comparative Example 5 and Example 2. Detailed Implementation

[0019] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0020] This embodiment provides a method for preparing an aqueous organic iron-based flow battery, including the following steps and process conditions: S1. Prepare a neutral salt solution using deionized water; In some specific embodiments, the neutral salt solution is an aqueous solution of NaCl, KCl, NaBr, NH4Cl, or NH4Br with a molar concentration of 0.1~2M.

[0021] In some specific embodiments of this application, a neutral salt solution is used as an activator. When the concentration of the neutral salt solution is too high, it easily induces the breakage of chemical bonds in the polymer backbone of the membrane matrix, with the breakage and decomposition of aromatic ether bonds and quaternary ammonium salt bonds being particularly significant. Simultaneously, it can lead to interlayer delamination of the membrane structure, excessive ionization of functional groups on the membrane surface, and consequently, damage to the microstructure of the membrane material, resulting in uneven pore size distribution and damage to the ion conduction channels within the membrane. These microstructural changes are reflected in the macroscopic properties of the membrane material, specifically manifested as a decrease in ion transport efficiency and a significant deterioration in the chemical stability of the membrane material.

[0022] When the concentration of the neutral salt solution is too low, the quaternary ammonium salt groups in the membrane material cannot be completely converted into active sites with ion exchange function, the degree of dissociation of sulfonic acid groups is insufficient, the construction process of ion conduction channels inside the membrane is inhibited, which leads to the ion conductivity not reaching the preset index and the ion selectivity being reduced.

[0023] S2. Preparation of the diaphragm: Immerse the anion exchange membrane in deionized water for 3-5 minutes to clean it; In some specific embodiments, the anion exchange membrane is selected from the AMVN anion exchange membrane manufactured by AGC Corporation of Japan; any other anion exchange membrane with equivalent functions or that can achieve the same technical effect falls within the protection scope defined by this embodiment.

[0024] S3. The anion exchange membrane obtained in step S2 is immersed in the neutral salt solution prepared in step S1 for ionization treatment. The immersion time is 1 to 48 hours, preferably 24 hours.

[0025] If the soaking time is too short, the degree of ionization conversion of functional groups in the membrane is insufficient, and its impact on membrane structure and performance is similar to that when the concentration of neutral salt solution is too low; if the soaking time is too long, it is easy to cause degradation of the polymer backbone of the membrane matrix and damage to the membrane microstructure, and its impact on membrane structure and performance is similar to that when the concentration of neutral salt solution is too high.

[0026] S4. Wash the diaphragm obtained in step S3 with deionized water 4 to 6 times, and finally soak it in deionized water for later use.

[0027] If the activator is not thoroughly cleaned and removed, the residual activator can continue to react with the membrane material, blocking the ion conduction channels already formed in the membrane, exacerbating the non-uniformity of the membrane microstructure, resulting in uneven pore size distribution and reduced ion conductivity. At the same time, the residual activator is prone to unexpected reactions with the subsequent working medium, generating insoluble precipitates, further blocking the membrane pores, and inducing localized corrosion or degradation hotspots.

[0028] S5. Prepare a neutral salt solution of the complex of ferrous compound and o-phenanthroline as the positive electrode active material; At room temperature, ferrous sulfate and o-phenanthroline were weighed separately and dissolved in the neutral salt solution obtained in step S1. The solution was stirred for 2 hours to obtain a neutral salt solution with a ferrous-o-phenanthroline complex concentration of 0.1-0.5 M, which was used as the positive electrode active material.

[0029] If the concentration of the complex formed by the ferrous compound and o-phenanthroline is too low, the content of effective active material in the system will be insufficient, and the most direct technical drawback will be a reduction in battery energy density. At the same time, the electrolyte ion concentration will decrease, leading to a reduction in ion transport efficiency. If the concentration of the complex is too high, the electrolyte viscosity will increase significantly, easily promoting the formation of gel deposits, which will cause pipeline blockage; and excessively high concentrations will also exacerbate the corrosive effect of the electrolyte on battery materials.

[0030] S6. A certain amount of EDTA is chelated with the positive electrode active material to prepare the positive electrode electrolyte; wherein the molar ratio of EDTA to o-phenanthroline is 1:1 to 1:3. If the concentration ratio of EDTA to the positive electrode active material is too high or too low, it will affect the chelation effect; when one of the substances is in excess, it will not be completely chelated and will leave residues, which are prone to causing unexpected side reactions during subsequent battery operation.

[0031] S7. Prepare a neutral salt solution of viologen derivatives as the negative electrode electrolyte; Viologen was added directly to a neutral salt solution (as a supporting electrolyte) with the same concentration as the positive electrode electrolyte at room temperature and stirred until the viologen was completely dissolved. The system was then transferred to a glove box and purged with argon gas for 40-50 minutes to completely remove oxygen from the solution.

[0032] In some specific embodiments, the viologen derivative is any one of MV, Dex-Vi, [(Me)(NPr)V]Cl3, [(NPr)2V]Br4, [(NPr)2TTz]Cl4, [(NPr)2PV]·4Cl, and [PyrPV]Cl4 with a molar concentration of 0.1~1M; the neutral aqueous solution is any one of NaCl, KCl, NaBr, NH4Cl, and NH4Br with a molar concentration of 0.1~1M.

[0033] S8. Use graphite felt or carbon felt as the electrode material of the battery; assemble the key materials obtained in S4~S8 into an aqueous organic iron-based redox flow battery system and test it using a battery testing system.

[0034] In some specific embodiments, the thickness of the graphite felt or carbon felt is 3-8 mm. If the thickness of the graphite felt or carbon felt is too large, the ohmic impedance of the electrode will increase, and its resistivity is positively correlated with the thickness; when the thickness exceeds 5 mm, the battery efficiency will decrease significantly. If the thickness is too small (less than 3 mm), the structural stability of the electrode will deteriorate, the utilization rate of the active material will decrease, and the local mass transfer resistance will increase, ultimately resulting in a decrease in battery efficiency.

[0035] A three-electrode system was used, with ferrous 1,1-diphenoxyacetate as the electroactive material, sodium chloride as the supporting electrolyte, a 3 mm glassy carbon electrode as the working electrode, silver / silver chloride as the reference electrode, and a platinum sheet as the counter electrode. Cyclic voltammetry was performed at a scan rate of 20 mV / s. Figure 1 The cyclic voltammetry curves shown are as follows.

[0036] Example 1

[0037] S1. Prepare a 1 mol / L NaCl aqueous solution using deionized water as a neutral salt solution for later use.

[0038] S2. Diaphragm pretreatment: An anion exchange membrane of model AMVN from AGC Corporation of Japan was selected and immersed in deionized water for 5 minutes.

[0039] S3, Ionization treatment: The anion exchange membrane obtained in step S2 was immersed in the 1 mol / L NaCl solution prepared in step S1 and soaked for 48 h for ionization treatment.

[0040] S4. Clean and set aside: The diaphragm obtained in step S3 was washed with deionized water 6 times and then soaked in deionized water for later use.

[0041] S5. Preparation of positive electrode active material: At room temperature, ferrous sulfate and o-phenanthroline were weighed separately and dissolved in the 1 mol / L NaCl solution prepared in step S1. The solution was stirred for 2 hours to obtain a ferrous-o-phenanthroline complex with a concentration of 0.1 mol / L. -1 A neutral salt solution is used as the positive electrode active material.

[0042] S6. Preparation of positive electrode electrolyte: EDTA was chelated and coordinated with the above-mentioned positive electrode active material to prepare a positive electrode electrolyte; wherein the molar ratio of EDTA to o-phenanthroline was 1:3.

[0043] S7. Preparation of negative electrode electrolyte: Methyl viologen (MV) was selected as the negative electrode active material. It was added to a 1 mol / L NaCl solution at room temperature and stirred until completely dissolved. Then, the solution was transferred to a glove box and purged with argon gas for 50 minutes to remove oxygen, yielding a methyl viologen concentration of 0.2 mol / L. -1 The negative electrode electrolyte.

[0044] S8. Battery Assembly and Testing: A carbon felt with a thickness of 8 mm was selected as the electrode material; the separator obtained in step S4, the positive electrode electrolyte obtained in step S6, and the negative electrode electrolyte obtained in step S7 were assembled into an aqueous organic iron-based redox flow single cell. A battery testing system was used to test the cell at 20 mA / cm². 2 Electrochemical performance was tested at a specific current density. The battery testing system used a 3mm glassy carbon electrode as the working electrode, silver / silver chloride as the reference electrode, and a platinum sheet as the counter electrode. Cyclic voltammetry was performed at a scan rate of 20mV / s. Figure 2 The figure shows the cycle efficiency of this embodiment. It can be seen that as the number of battery cycles increases, the coulombic efficiency remains relatively stable, consistently above 90%, indicating a high overall level of coulombic efficiency.

[0045] Example 2

[0046] S1. Prepare a 1 mol / L NaCl aqueous solution using deionized water as a neutral salt solution for later use.

[0047] S2. Membrane pretreatment: Select an anion exchange membrane of model AMVN from AGC Corporation of Japan and soak it in deionized water for 4 minutes.

[0048] S3. Ionization treatment: Immerse the anion exchange membrane obtained in step S2 into the 1 mol / L NaCl solution prepared in step S1 and soak for 24 h for ionization treatment.

[0049] S4. Cleaning and setting aside: Wash the diaphragm obtained in step S3 with deionized water 5 times, and then soak it in deionized water for later use.

[0050] S5. Preparation of positive electrode active material: At room temperature, ferrous sulfate and o-phenanthroline were weighed and dissolved in the 1 mol / L NaCl solution obtained in step S1. The solution was stirred for 2 h to obtain a neutral salt solution with a ferrous-o-phenanthroline complex concentration of 0.1 mol / L, which was used as the positive electrode active material.

[0051] S6. Preparation of positive electrode electrolyte: EDTA is chelated and coordinated with the above-mentioned positive electrode active material to prepare a positive electrode electrolyte; wherein the molar ratio of EDTA to o-phenanthroline is 1:2.

[0052] S7. Preparation of negative electrode electrolyte: Methyl viologen (MV) was selected as the negative electrode active material. It was added to a 1 mol / L NaCl solution at room temperature and stirred until completely dissolved. Then it was transferred to a glove box and argon gas was introduced for 45 min to remove oxygen, so as to obtain a negative electrode electrolyte with a methyl viologen concentration of 0.15 mol / L.

[0053] S8. Battery Assembly and Testing: A 5.5mm thick carbon felt was selected as the electrode material. The separator obtained in step S4, the positive electrolyte obtained in step S6, and the negative electrolyte obtained in step S7 were assembled into an aqueous organic iron-based redox flow single cell. A battery testing system was used at 20mA / cm². 2 Electrochemical performance was tested at a specific current density. A three-electrode system was constructed using a 3mm glassy carbon electrode as the working electrode, silver / silver chloride as the reference electrode, and a platinum sheet as the counter electrode. Cyclic voltammetry was performed at a scan rate of 20 mV / s. Figure 3 The figure shows the cycle efficiency graph for this embodiment. The coulombic efficiency remains stable in the range of 93%-96% with very little fluctuation; the energy efficiency remains stable in the range of 76%-78%, with only a slight decrease after 20 cycles, and the curve is generally flat.

[0054] Example 3

[0055] S1. Prepare a 1 mol / L NaCl aqueous solution using deionized water as a neutral salt solution for later use.

[0056] S2. Membrane pretreatment: Select an anion exchange membrane of model AMVN from AGC Corporation of Japan and soak it in deionized water for 3 minutes.

[0057] S3. Ionization treatment: Immerse the anion exchange membrane obtained in step S2 into the 1 mol / L NaCl solution prepared in step S1 and soak for 1 h to perform ionization treatment.

[0058] S4. Cleaning and setting aside: The diaphragm obtained in step S3 is cleaned 4 times with deionized water and then soaked in deionized water for later use.

[0059] S5. Preparation of positive electrode active material: At room temperature, ferrous sulfate and o-phenanthroline were weighed and dissolved in the 1 mol / L NaCl solution obtained in step S1. The solution was stirred for 2 h to obtain a neutral salt solution with a ferrous-o-phenanthroline complex concentration of 0.1 mol / L, which was used as the positive electrode active material.

[0060] S6. Preparation of positive electrode electrolyte: EDTA is chelated and coordinated with the above-mentioned positive electrode active material to prepare a positive electrode electrolyte; wherein the molar ratio of EDTA to o-phenanthroline is 1:1.

[0061] S7. Preparation of negative electrode electrolyte: Dex-Vi was selected as the negative electrode active material. It was added to a 1 mol / L NaCl solution at room temperature and stirred until completely dissolved. Then it was transferred to a glove box and argon gas was introduced for 40 min to remove oxygen, so as to obtain a negative electrode electrolyte with a Dex-Vi concentration of 0.2 mol / L.

[0062] S8. Battery Assembly and Testing: 3mm thick carbon felt was selected as the electrode material; the separator obtained in step S4, the positive electrolyte obtained in step S6, and the negative electrolyte obtained in step S7 were assembled into an aqueous organic iron-based redox flow single cell. A battery testing system was used at 20mA / cm². 2 Electrochemical performance was tested at a specific current density. A three-electrode system was constructed using a 3mm glassy carbon electrode as the working electrode, silver / silver chloride as the reference electrode, and a platinum sheet as the counter electrode. Cyclic voltammetry was performed at a scan rate of 20 mV / s. Figure 4 The diagram shown is the cycle efficiency diagram of this embodiment; the coulomb efficiency is maintained at 92%-95%.

[0063] Example 4

[0064] S1. Prepare a 1 mol / L NaCl aqueous solution using deionized water as a neutral salt solution for later use.

[0065] S2. Membrane pretreatment: Select an anion exchange membrane of model AMVN from AGC Corporation of Japan and soak it in deionized water for 4 minutes.

[0066] S3. Ionization treatment: Immerse the anion exchange membrane obtained in step S2 into the 1 mol / L NaCl solution prepared in step S1 and soak for 24 h for ionization treatment.

[0067] S4. Cleaning and setting aside: Wash the diaphragm obtained in step S3 with deionized water 5 times, and then soak it in deionized water for later use.

[0068] S5. Preparation of positive electrode active material: At room temperature, ferrous sulfate and o-phenanthroline were weighed and dissolved in the 1 mol / L NaCl solution obtained in step S1. The solution was stirred for 2 h to obtain a neutral salt solution with a ferrous-o-phenanthroline complex concentration of 0.1 mol / L, which was used as the positive electrode active material.

[0069] S6. Preparation of positive electrode electrolyte: EDTA is chelated and coordinated with the above-mentioned positive electrode active material to prepare a positive electrode electrolyte; wherein the molar ratio of EDTA to o-phenanthroline is 1:2.

[0070] S7. Preparation of negative electrode electrolyte: Dex-Vi was selected as the negative electrode active material. It was added to a 1 mol / L NaCl solution at room temperature and stirred until completely dissolved. Then it was transferred to a glove box and purged with argon gas for 45 min to remove oxygen, thus obtaining a negative electrode electrolyte with a Dex-Vi concentration of 0.15 mol / L.

[0071] S8. Battery Assembly and Testing: A 5.5mm thick carbon felt was selected as the electrode material. The separator obtained in step S4, the positive electrolyte obtained in step S6, and the negative electrolyte obtained in step S7 were assembled into an aqueous organic iron-based redox flow single cell. A battery testing system was used at 20mA / cm². 2 Electrochemical performance was tested at a specific current density. A three-electrode system was constructed using a 3mm glassy carbon electrode as the working electrode, silver / silver chloride as the reference electrode, and a platinum sheet as the counter electrode. Cyclic voltammetry was performed at a scan rate of 20 mV / s. Figure 5 The figure shows the cycle efficiency of this embodiment. The coulombic efficiency is close to 98%, with almost no decay; the energy efficiency remains stable at 77-81%, with only a slight drop after 20 cycles, and the curve is very smooth overall. The Dex-Vi modified viologen molecule has greater steric hindrance, further suppressing transmembrane permeation; the membrane, EDTA ratio, and electrode all use optimal parameters; the coulombic efficiency is better than that of the methyl viologen (MV) system, proving that Dex-Vi, as the negative electrode active material, can achieve better ion barrier and cycle stability under this complete process.

[0072] Example 5

[0073] S1. Prepare a 1 mol / L NaCl aqueous solution using deionized water as a neutral salt solution for later use.

[0074] S2. Membrane pretreatment: Select an anion exchange membrane of model AMVN from AGC Corporation of Japan and soak it in deionized water for 4 minutes.

[0075] S3. Ionization treatment: Immerse the anion exchange membrane obtained in step S2 into the 1 mol / L NaCl solution prepared in step S1 and soak for 24 h for ionization treatment.

[0076] S4. Cleaning and setting aside: Wash the diaphragm obtained in step S3 with deionized water 5 times, and then soak it in deionized water for later use.

[0077] S5. Preparation of positive electrode active material: At room temperature, ferrous sulfate and o-phenanthroline were weighed and dissolved in the 1 mol / L NaCl solution obtained in step S1. The solution was stirred for 2 h to obtain a neutral salt solution with a ferrous-o-phenanthroline complex concentration of 0.1 mol / L, which was used as the positive electrode active material.

[0078] S6. Preparation of positive electrode electrolyte: EDTA is chelated and coordinated with the above-mentioned positive electrode active material to prepare a positive electrode electrolyte; wherein the molar ratio of EDTA to o-phenanthroline is 1:2.

[0079] S7. Preparation of negative electrode electrolyte: Select [(Me)(NPr)V]Cl3 as the negative electrode active material, add it to 1 mol / L NaCl solution at room temperature and stir until completely dissolved; then transfer it to a glove box and purge it with argon gas for 45 min to remove oxygen, and obtain a negative electrode electrolyte with a [(Me)(NPr)V]Cl3 concentration of 0.2 mol / L.

[0080] S8. Battery Assembly and Testing: A 5.5mm thick carbon felt was selected as the electrode material. The separator obtained in step S4, the positive electrolyte obtained in step S6, and the negative electrolyte obtained in step S7 were assembled into an aqueous organic iron-based redox flow single cell. A battery testing system was used at 20mA / cm². 2 Electrochemical performance was tested at a specific current density. A three-electrode system was constructed using a 3mm glassy carbon electrode as the working electrode, silver / silver chloride as the reference electrode, and a platinum sheet as the counter electrode. Cyclic voltammetry was performed at a scan rate of 20 mV / s. Figure 6 The diagram shows the cycle efficiency of this embodiment. The coulombic efficiency remained stable at 92-96%; the energy efficiency started at approximately 68-70%, decreasing slowly with each cycle, reaching around 63% after 20 cycles. The electrochemical reversibility of this propyl-substituted viologen derivative was weaker than that of Dex-Vi; although the membrane, cathode, and electrode conditions were all optimal, the anode itself exhibited certain side reactions, resulting in an overall energy efficiency lower than the Dex-Vi system, although the coulombic efficiency remained relatively high.

[0081] Example 6

[0082] S1. Prepare a 1 mol / L NaCl aqueous solution using deionized water as a neutral salt solution for later use.

[0083] S2. Membrane pretreatment: Select an anion exchange membrane of model AMVN from AGC Corporation of Japan and soak it in deionized water for 4 minutes.

[0084] S3. Ionization treatment: Immerse the anion exchange membrane obtained in step S2 into the 1 mol / L NaCl solution prepared in step S1 and soak for 24 h for ionization treatment.

[0085] S4. Cleaning and setting aside: Wash the diaphragm obtained in step S3 with deionized water 5 times, and then soak it in deionized water for later use.

[0086] S5. Preparation of positive electrode active material: At room temperature, ferrous sulfate and o-phenanthroline were weighed and dissolved in the 1 mol / L NaCl solution obtained in step S1. The solution was stirred for 2 h to obtain a neutral salt solution with a ferrous-o-phenanthroline complex concentration of 0.05 mol / L, which was used as the positive electrode active material.

[0087] S6. Preparation of positive electrode electrolyte: EDTA is chelated and coordinated with the above-mentioned positive electrode active material to prepare a positive electrode electrolyte; wherein the molar ratio of EDTA to o-phenanthroline is 1:2.

[0088] S7. Preparation of negative electrode electrolyte: Methyl viologen (MV) was selected as the negative electrode active material. It was added to a 1 mol / L NaCl solution at room temperature and stirred until completely dissolved. Then it was transferred to a glove box and argon gas was introduced for 45 min to remove oxygen, so as to obtain a negative electrode electrolyte with a methyl viologen concentration of 0.1 mol / L.

[0089] S8. Battery Assembly and Testing: A 5.5mm thick carbon felt was selected as the electrode material. The separator obtained in step S4, the positive electrolyte obtained in step S6, and the negative electrolyte obtained in step S7 were assembled into an aqueous organic iron-based redox flow single cell. A battery testing system was used at 20mA / cm². 2 Electrochemical performance was tested at a specific current density. A three-electrode system was constructed using a 3mm glassy carbon electrode as the working electrode, silver / silver chloride as the reference electrode, and a platinum sheet as the counter electrode. Cyclic voltammetry was performed at a scan rate of 20 mV / s. Figure 7 The diagram shown is a cycle efficiency graph for this embodiment. The coulombic efficiency is 93-97%.

[0090] Example 7

[0091] S1. Prepare a 1 mol / L NaBr aqueous solution using deionized water as a neutral salt solution for later use.

[0092] S2. Membrane pretreatment: Select an anion exchange membrane of model AMVN from AGC Corporation of Japan and soak it in deionized water for 4 minutes.

[0093] S3. Ionization treatment: Immerse the anion exchange membrane obtained in step S2 into the 1 mol / L NaBr solution prepared in step S1 and soak for 24 h for ionization treatment.

[0094] S4. Cleaning and setting aside: Wash the diaphragm obtained in step S3 with deionized water 5 times, and then soak it in deionized water for later use.

[0095] S5. Preparation of positive electrode active material: At room temperature, ferrous sulfate and o-phenanthroline were weighed and dissolved in the 1 mol / L NaBr solution obtained in step S1. The solution was stirred for 2 h to obtain a neutral salt solution with a ferrous-o-phenanthroline complex concentration of 0.1 mol / L, which was used as the positive electrode active material.

[0096] S6. Preparation of positive electrode electrolyte: EDTA is chelated and coordinated with the above-mentioned positive electrode active material to prepare a positive electrode electrolyte; wherein the molar ratio of EDTA to o-phenanthroline is 1:2.

[0097] S7. Preparation of negative electrode electrolyte: Methyl viologen (MV) was selected as the negative electrode active material. It was added to a 1 mol / L NaBr solution at room temperature and stirred until completely dissolved. Then it was transferred to a glove box and purged with argon gas for 45 min to remove oxygen, thus obtaining a negative electrode electrolyte with a methyl viologen concentration of 0.2 mol / L.

[0098] S8. Battery Assembly and Testing: A 5.5mm thick carbon felt was selected as the electrode material. The separator obtained in step S4, the positive electrolyte obtained in step S6, and the negative electrolyte obtained in step S7 were assembled into an aqueous organic iron-based redox flow single cell. A battery testing system was used at 20mA / cm². 2 Electrochemical performance was tested at a specific current density. A three-electrode system was constructed using a 3mm glassy carbon electrode as the working electrode, silver / silver chloride as the reference electrode, and a platinum sheet as the counter electrode. Cyclic voltammetry was performed at a scan rate of 20 mV / s. Figure 8 The diagram shown illustrates the cycle efficiency of this embodiment. The coulombic efficiency is 93-98%, with minimal fluctuation; the energy efficiency remains stable at 75-79%, with only a small decay over 20 cycles. NaBr can be used as a feasible neutral supporting salt in this invention; the membrane ionization effect is good under the Br⁻ anion system, and the electrolyte conductivity is excellent.

[0099] Example 8

[0100] S1. Prepare a 1 mol / L KCl aqueous solution using deionized water as a neutral salt solution for later use.

[0101] S2. Membrane pretreatment: Select an anion exchange membrane of model AMVN from AGC Corporation of Japan and soak it in deionized water for 4 minutes.

[0102] S3. Ionization treatment: Immerse the anion exchange membrane obtained in step S2 into the 1 mol / L KCl solution prepared in step S1 and soak for 24 h for ionization treatment.

[0103] S4. Cleaning and setting aside: Wash the diaphragm obtained in step S3 with deionized water 5 times, and then soak it in deionized water for later use.

[0104] S5. Preparation of positive electrode active material: At room temperature, ferrous sulfate and o-phenanthroline were weighed and dissolved in the 1 mol / L KCl solution obtained in step S1. The solution was stirred for 2 h to obtain a neutral salt solution with a ferrous-o-phenanthroline complex concentration of 0.1 mol / L, which was used as the positive electrode active material.

[0105] S6. Preparation of positive electrode electrolyte: EDTA is chelated and coordinated with the above-mentioned positive electrode active material to prepare a positive electrode electrolyte; wherein the molar ratio of EDTA to o-phenanthroline is 1:2.

[0106] S7. Preparation of negative electrode electrolyte: Methyl viologen (MV) was selected as the negative electrode active material. It was added to a 1 mol / L KCl solution at room temperature and stirred until completely dissolved. Then it was transferred to a glove box and purged with argon gas for 45 min to remove oxygen, thus obtaining a negative electrode electrolyte with a methyl viologen concentration of 0.2 mol / L.

[0107] S8. Battery Assembly and Testing: A 5.5mm thick carbon felt was selected as the electrode material. The separator obtained in step S4, the positive electrolyte obtained in step S6, and the negative electrolyte obtained in step S7 were assembled into an aqueous organic iron-based redox flow single cell. A battery testing system was used at 20mA / cm². 2 Electrochemical performance was tested at a specific current density. A three-electrode system was constructed using a 3mm glassy carbon electrode as the working electrode, silver / silver chloride as the reference electrode, and a platinum sheet as the counter electrode. Cyclic voltammetry was performed at a scan rate of 20 mV / s. Figure 9 The diagram shown is a cycle efficiency graph for this embodiment. The coulombic efficiency remains at 92-97%; the energy efficiency is stable at 76-79%, with only slight decay after 20 cycles.

[0108] Example 9

[0109] S1. Prepare a 1 mol / L NaCl aqueous solution using deionized water as a neutral salt solution for later use.

[0110] S2. Membrane pretreatment: Select an anion exchange membrane of model AMVN from AGC Corporation of Japan and soak it in deionized water for 4 minutes.

[0111] S3. Ionization treatment: Immerse the anion exchange membrane obtained in step S2 into the 1 mol / L NaCl solution prepared in step S1 and soak for 24 h for ionization treatment.

[0112] S4. Cleaning and setting aside: Wash the diaphragm obtained in step S3 with deionized water 5 times, and then soak it in deionized water for later use.

[0113] S5. Preparation of positive electrode active material: At room temperature, ferrous sulfate and o-phenanthroline were weighed and dissolved in the 1 mol / L NaCl solution obtained in step S1. The solution was stirred for 2 h to obtain a neutral salt solution with a ferrous-o-phenanthroline complex concentration of 0.2 mol / L, which was used as the positive electrode active material.

[0114] S6. Preparation of positive electrode electrolyte: EDTA is chelated and coordinated with the above-mentioned positive electrode active material to prepare a positive electrode electrolyte; wherein the molar ratio of EDTA to o-phenanthroline is 1:2.

[0115] S7. Preparation of negative electrode electrolyte: Dex-Vi was selected as the negative electrode active material. It was added to a 1 mol / L NaCl solution at room temperature and stirred until completely dissolved. Then it was transferred to a glove box and purged with argon gas for 45 min to remove oxygen, thus obtaining a negative electrode electrolyte with a Dex-Vi concentration of 0.3 mol / L.

[0116] S8. Battery Assembly and Testing: A 5.5mm thick carbon felt was selected as the electrode material. The separator obtained in step S4, the positive electrolyte obtained in step S6, and the negative electrolyte obtained in step S7 were assembled into an aqueous organic iron-based redox flow single cell. A battery testing system was used at 20mA / cm². 2 Electrochemical performance was tested at a specific current density. A three-electrode system was constructed using a 3mm glassy carbon electrode as the working electrode, silver / silver chloride as the reference electrode, and a platinum sheet as the counter electrode. Cyclic voltammetry was performed at a scan rate of 20 mV / s. Figure 10 The figure shows the cycle efficiency of this embodiment. The coulombic efficiency is 93-97%; the energy efficiency is 72-76%, with only a slight decrease after 20 cycles, and the curve is generally stable. Increasing the concentration of active materials at both the positive and negative electrodes increases the theoretical energy density of the system; the increased concentration of active materials causes a slight increase in electrolyte viscosity, and the polarization is slightly higher than the 0.1M positive electrode reference; good cycle stability is maintained.

[0117] Example 10

[0118] S1. Prepare a 2 mol / L NaCl aqueous solution using deionized water as a neutral salt solution for later use.

[0119] S2. Membrane pretreatment: Select an anion exchange membrane of model AMVN from AGC Corporation of Japan and soak it in deionized water for 4 minutes.

[0120] S3. Ionization treatment: Immerse the anion exchange membrane obtained in step S2 into the 2 mol / L NaCl solution prepared in step S1 and soak for 24 h for ionization treatment.

[0121] S4. Cleaning and setting aside: Wash the diaphragm obtained in step S3 with deionized water 5 times, and then soak it in deionized water for later use.

[0122] S5. Preparation of positive electrode active material: At room temperature, ferrous sulfate and o-phenanthroline were weighed and dissolved in the 2 mol / L NaCl solution obtained in step S1. The solution was stirred for 2 h to obtain a neutral salt solution with a ferrous-o-phenanthroline complex concentration of 0.1 mol / L, which was used as the positive electrode active material.

[0123] S6. Preparation of positive electrode electrolyte: EDTA is chelated and coordinated with the above-mentioned positive electrode active material to prepare a positive electrode electrolyte; wherein the molar ratio of EDTA to o-phenanthroline is 1:2.

[0124] S7. Preparation of negative electrode electrolyte: Methyl viologen (MV) was selected as the negative electrode active material. It was added to a 2 mol / L NaCl solution at room temperature and stirred until completely dissolved. Then it was transferred to a glove box and argon gas was introduced for 45 min to remove oxygen, so as to obtain a negative electrode electrolyte with a methyl viologen concentration of 0.2 mol / L.

[0125] S8. Battery Assembly and Testing: A 5.5mm thick carbon felt was selected as the electrode material. The separator obtained in step S4, the positive electrolyte obtained in step S6, and the negative electrolyte obtained in step S7 were assembled into an aqueous organic iron-based redox flow single cell. A battery testing system was used at 20mA / cm². 2 Electrochemical performance was tested at a specific current density. A three-electrode system was constructed using a 3mm glassy carbon electrode as the working electrode, silver / silver chloride as the reference electrode, and a platinum sheet as the counter electrode. Cyclic voltammetry was performed at a scan rate of 20 mV / s. Figure 11 The diagram shown is a cycle efficiency graph for this embodiment. The Coulomb efficiency is close to 99% in the early stage.

[0126] Example 11

[0127] S1. Prepare a 1 mol / L NH4Cl aqueous solution using deionized water as a neutral salt solution for later use.

[0128] S2. Membrane pretreatment: Select an anion exchange membrane of model AMVN from AGC Corporation of Japan and soak it in deionized water for 4 minutes.

[0129] S3. Ionization treatment: Immerse the anion exchange membrane obtained in step S2 into the 1 mol / L NH4Cl solution prepared in step S1 and soak for 24 h for ionization treatment.

[0130] S4. Cleaning and setting aside: Wash the diaphragm obtained in step S3 with deionized water 5 times, and then soak it in deionized water for later use.

[0131] S5. Preparation of positive electrode active material: At room temperature, ferrous sulfate and o-phenanthroline were weighed and dissolved in the 1 mol / L NH4Cl solution obtained in step S1. The solution was stirred for 2 h to obtain a neutral salt solution with a ferrous-o-phenanthroline complex concentration of 0.1 mol / L, which was used as the positive electrode active material.

[0132] S6. Preparation of positive electrode electrolyte: EDTA is chelated and coordinated with the above-mentioned positive electrode active material to prepare a positive electrode electrolyte; wherein the molar ratio of EDTA to o-phenanthroline is 1:2.

[0133] S7. Preparation of negative electrode electrolyte: Select [(NPr)2V]Br4 as the negative electrode active material, add it to 1 mol / L NH4Cl solution at room temperature, and stir until completely dissolved; then transfer it to a glove box and purge it with argon gas for 45 min to remove oxygen, and obtain a negative electrode electrolyte with a [(NPr)2V]Br4 concentration of 0.2 mol / L.

[0134] S8. Carbon felt with a thickness of 5.5 mm is selected as the electrode material for battery assembly; the separator obtained in step S4, the positive electrolyte obtained in step S6, and the negative electrolyte obtained in step S7 are assembled into an aqueous organic iron-based redox flow single cell.

[0135] Example 12

[0136] S1. Prepare a 1 mol / L NH4Br aqueous solution using deionized water as a neutral salt solution for later use.

[0137] S2. Membrane pretreatment: Select an anion exchange membrane of model AMVN from AGC Corporation of Japan and soak it in deionized water for 4 minutes.

[0138] S3. Ionization treatment: Immerse the anion exchange membrane obtained in step S2 into the 1 mol / L NH4Br solution prepared in step S1 and soak for 24 h for ionization treatment.

[0139] S4. Cleaning and setting aside: Wash the diaphragm obtained in step S3 with deionized water 5 times, and then soak it in deionized water for later use.

[0140] S5. Preparation of positive electrode active material: At room temperature, ferrous sulfate and o-phenanthroline were weighed and dissolved in the 1 mol / L NH4Br solution obtained in step S1. The solution was stirred for 2 h to obtain a neutral salt solution with a ferrous-o-phenanthroline complex concentration of 0.1 mol / L, which was used as the positive electrode active material.

[0141] S6. Preparation of positive electrode electrolyte: EDTA is chelated and coordinated with the above-mentioned positive electrode active material to prepare a positive electrode electrolyte; wherein the molar ratio of EDTA to o-phenanthroline is 1:2.

[0142] S7. Preparation of negative electrode electrolyte: Select [(NPr)2TTz]Cl4 as the negative electrode active material, add it to 1 mol / L NH4Br solution at room temperature, and stir until completely dissolved; then transfer it to a glove box and purge it with argon gas for 45 min to remove oxygen, and obtain a negative electrode electrolyte with a [(NPr)2TTz]Cl4 concentration of 0.2 mol / L.

[0143] S8. Carbon felt with a thickness of 5.5 mm is selected as the electrode material for battery assembly; the separator obtained in step S4, the positive electrolyte obtained in step S6, and the negative electrolyte obtained in step S7 are assembled into an aqueous organic iron-based redox flow single cell.

[0144] Example 13

[0145] S1. Prepare a 1 mol / L NaCl aqueous solution using deionized water as a neutral salt solution for later use.

[0146] S2. Membrane pretreatment: Select an anion exchange membrane of model AMVN from AGC Corporation of Japan and soak it in deionized water for 4 minutes.

[0147] S3. Ionization treatment: Immerse the anion exchange membrane obtained in step S2 into the 1 mol / L NaCl solution prepared in step S1 and soak for 24 h for ionization treatment.

[0148] S4. Cleaning and setting aside: Wash the diaphragm obtained in step S3 with deionized water 5 times, and then soak it in deionized water for later use.

[0149] S5. Preparation of positive electrode active material: At room temperature, ferrous sulfate and o-phenanthroline were weighed and dissolved in the 1 mol / L NaCl solution obtained in step S1. The solution was stirred for 2 h to obtain a neutral salt solution with a ferrous-o-phenanthroline complex concentration of 0.1 mol / L, which was used as the positive electrode active material.

[0150] S6. Preparation of positive electrode electrolyte: EDTA is chelated and coordinated with the above-mentioned positive electrode active material to prepare a positive electrode electrolyte; wherein the molar ratio of EDTA to o-phenanthroline is 1:2.

[0151] S7. Preparation of negative electrode electrolyte: Select [(NPr)2PV]·4Cl as the negative electrode active material, add it to 1 mol / L NaCl solution at room temperature and stir until completely dissolved; then transfer it to a glove box and purge it with argon gas for 45 min to remove oxygen, and obtain a negative electrode electrolyte with a [(NPr)2PV]·4Cl concentration of 0.2 mol / L.

[0152] S8. Carbon felt with a thickness of 5.5 mm is selected as the electrode material for battery assembly; the separator obtained in step S4, the positive electrolyte obtained in step S6, and the negative electrolyte obtained in step S7 are assembled into an aqueous organic iron-based redox flow single cell.

[0153] Example 14

[0154] S1. Prepare a 1 mol / L NaCl aqueous solution using deionized water as a neutral salt solution for later use.

[0155] S2. Membrane pretreatment: Select an anion exchange membrane of model AMVN from AGC Corporation of Japan and soak it in deionized water for 4 minutes.

[0156] S3. Ionization treatment: Immerse the anion exchange membrane obtained in step S2 into the 1 mol / L NaCl solution prepared in step S1 and soak for 24 h for ionization treatment.

[0157] S4. Cleaning and setting aside: Wash the diaphragm obtained in step S3 with deionized water 5 times, and then soak it in deionized water for later use.

[0158] S5. Preparation of positive electrode active material: At room temperature, ferrous sulfate and o-phenanthroline were weighed and dissolved in the 1 mol / L NaCl solution obtained in step S1. The solution was stirred for 2 h to obtain a neutral salt solution with a ferrous-o-phenanthroline complex concentration of 0.1 mol / L, which was used as the positive electrode active material.

[0159] S6. Preparation of positive electrode electrolyte: EDTA is chelated and coordinated with the above-mentioned positive electrode active material to prepare a positive electrode electrolyte; wherein the molar ratio of EDTA to o-phenanthroline is 1:2.

[0160] S7. Preparation of negative electrode electrolyte: [PyrPV]Cl4 was selected as the negative electrode active material. It was added to a 1 mol / L NaCl solution at room temperature and stirred until completely dissolved. Then it was transferred to a glove box and argon gas was introduced for 45 min to remove oxygen, so as to obtain a negative electrode electrolyte with a [PyrPV]Cl4 concentration of 0.2 mol / L.

[0161] S8. Carbon felt with a thickness of 5.5 mm is selected as the electrode material for battery assembly; the separator obtained in step S4, the positive electrolyte obtained in step S6, and the negative electrolyte obtained in step S7 are assembled into an aqueous organic iron-based redox flow single cell.

[0162] Example 15

[0163] S1. Prepare a 1 mol / L NaCl aqueous solution using deionized water as a neutral salt solution for later use.

[0164] S2. Diaphragm pretreatment: An anion exchange membrane of model AMVN from AGC Corporation of Japan was selected and immersed in deionized water for 5 minutes.

[0165] S3, Ionization treatment: The anion exchange membrane obtained in step S2 was immersed in the 1 mol / L NaCl solution prepared in step S1 and soaked for 48 h for ionization treatment.

[0166] S4. Clean and set aside: The diaphragm obtained in step S3 was washed with deionized water 6 times and then soaked in deionized water for later use.

[0167] S5. Preparation of positive electrode active material: At room temperature, ferrous sulfate and o-phenanthroline were weighed separately and dissolved in the 1 mol / L NaCl solution prepared in step S1. The solution was stirred for 2 h to obtain a neutral salt solution with a ferrous-o-phenanthroline complex concentration of 0.5 mol / L, which was used as the positive electrode active material.

[0168] S6. Preparation of positive electrode electrolyte: EDTA was chelated and coordinated with the above-mentioned positive electrode active material to prepare a positive electrode electrolyte; wherein the molar ratio of EDTA to o-phenanthroline was 1:3.

[0169] S7. Preparation of negative electrode electrolyte: Methyl viologen (MV) was selected as the negative electrode active material. It was added to a 1 mol / L NaCl solution at room temperature and stirred until completely dissolved. Then it was transferred to a glove box and purged with argon gas for 50 min to remove oxygen, thus obtaining a negative electrode electrolyte with a methyl viologen concentration of 1 mol / L.

[0170] S8. Battery Assembly and Testing: A carbon felt with a thickness of 8 mm was selected as the electrode material; the separator obtained in step S4, the positive electrode electrolyte obtained in step S6, and the negative electrode electrolyte obtained in step S7 were assembled into an aqueous organic iron-based redox flow single cell. A battery testing system was used to test the cell at 20 mA / cm². 2 Electrochemical performance was tested at current density.

[0171] Baseline Implementation (Example 2, Optimal Parameters) S1: 1M NaCl; S2: AMVN membrane water wash for 4 min; S3: Salt solution soak for 24 h; S4: Water wash 5 times; S5: 0.1M Fe-phen; S6: EDTA:phen = 1:2; S7: 0.15M MMV, Ar deoxygenation for 45 min; S8: 5.5mm carbon felt.

[0172] Test conditions: 20mA / cm 2 Glove box with Ar protection, voltage 0~1.65V, 20 cycles.

[0173] Performance results: Average coulombic efficiency (CE) = 96.2%, average energy efficiency (EE) = 78.5%; capacity retention after 20 cycles: 76.3%; no pipe / carbon felt deposition or blockage in the battery; no red precipitate in the separator; no obvious turbidity in the electrolyte.

[0174] Comparative Example 1: Conventional Fe-phen / MV batteries with EDTA-free, pure water pre-treated separators (industry benchmark comparison) The membrane was soaked in deionized water for 24 hours without the NaCl ionization step; the S6EDTA chelation step was omitted, and Fe-phen solution was used directly as the positive electrode electrolyte; the remaining parameters were the same as in the baseline example 2.

[0175] Test conditions: Current density 20 mA / cm² 2 The test was performed in an argon glove box environment, 20 cycles. Figure 12 As shown; average CE=82.1%, average EE=54.7%; capacity retention rate after 20 cycles: 31.2%; battery disassembly: the separator is covered with red Fe-phen precipitate, and a large amount of solids are precipitated on the surface of the carbon felt; the internal resistance continues to rise from 220mΩ to 410mΩ; after 10 cycles, the discharge capacity is only 40% of the initial capacity.

[0176] like Figure 13 Comparative Example 1 lacks EDTA chelation and cannot stabilize Fe. 3+ High-valence iron continued to precipitate; the unactivated ion conduction channels of the separator were missing, and the active material transmembrane was severely affected, resulting in rapid capacity decay. This proves that EDTA chelation and salt solution ionization of the separator play an indispensable synergistic role in inhibiting iron ion precipitation, blocking the transmembrane shuttle of active material, and maintaining the long-cycle capacity stability of the battery.

[0177] Comparative Example 2: Neutral salt concentration is higher than the preferred range (2M NaCl, upper limit of parameter). Process modification: The neutral salt S1 was replaced with 2M NaCl, otherwise the process was the same as in baseline Example 2.

[0178] Test conditions: Current density 20 mA / cm²2 The test was performed in an argon glove box environment, 20 cycles. Figure 14 As shown, the average CE was 90.5% and the average EE was 67.1%; the capacity retention rate after 20 cycles was 52.8%; the electrolyte showed slight turbidity after standing, and a small amount of white sodium salt precipitate appeared at the carbon felt inlet; under high salt conditions, Na⁺ coordinated with o-phenanthroline to form an insoluble complex, and the effective concentration of Fe-phen continued to decrease.

[0179] like Figure 15 When the salt concentration exceeds 1M, excess Na⁺ and phen ligands precipitate. At the same time, high salt concentration damages the microstructure of the anion exchange membrane, resulting in uneven membrane pores, decreased ion selectivity, and significantly lower efficiency and capacity retention compared to the optimal 1M system.

[0180] Comparative Example 3: Neutral salt concentration below the preferred range (0.1M NaCl, lower limit of parameter) Process modification: S1 neutral salt solution 0.1 mol / L NaCl, all other parameters remain the same as in Example 2.

[0181] Test conditions: Current density 20 mA / cm² 2 The test was performed in an argon glove box environment, 20 cycles. Figure 16 , Figure 17 As shown, when the neutral salt concentration drops to the lower limit of 0.1M, the membrane activation is insufficient, the electrolyte conductivity is inadequate, and the polarization loss increases significantly. The three core performance indicators—coulombic efficiency, energy efficiency, and capacity retention—are all inferior to the optimal system of 1M NaCl. This verifies that within the concentration range of 0.1~2M, 1M NaCl is the optimal supporting electrolyte concentration that simultaneously takes into account the degree of membrane ion activation, electrolyte solubility, and electrochemical conductivity.

[0182] Comparative Example 4 (diaphragm ionization soaking time of 60h, exceeding the preferred upper limit) Process modification: The S3 diaphragm was soaked in neutral salt for 60 hours. All other processes, material concentrations, and electrode parameters were exactly the same as in Example 2, corresponding to the process conditions of Patent Example 1.

[0183] Test conditions: Current density 20 mA / cm² 2 Circulate 20 times, with argon gas glove box for protection.

[0184] like Figure 18 , 19As shown, extending the ionization soaking time of the diaphragm to 60 hours will cause irreversible degradation of the polymer matrix of the anion exchange membrane, membrane peeling, and a simultaneous decrease in ion selectivity and ion conductivity. The three core performance indicators, coulombic efficiency, energy efficiency, and capacity retention, are all significantly lower than the optimal process of 24 hours of soaking. It is verified that within the soaking range of 1 to 48 hours, 24 hours is the preferred soaking time that simultaneously ensures sufficient ion activation of the diaphragm and the integrity of the diaphragm microstructure.

[0185] Comparative Example 5 (with the S6EDTA chelation preparation step removed) Process modification: The S6EDTA chelation preparation step was deleted, and the S5 ferrous phenanthrene complex solution was directly used as the positive electrode electrolyte. The remaining membrane pretreatment, salt concentration, negative electrode solution, and electrode parameters were completely consistent with those in Example 2.

[0186] Test conditions: Current density 20 mA / cm² 2 Circulate 20 times, with argon gas glove box for protection.

[0187] like Figure 20 , Figure 21 As shown, without the EDTA chelation process, the ferric ions lack stable ligand protection, and solid precipitates are continuously degraded by water during cycling, resulting in severe irreversible loss of the positive electrode active material. The battery's three core performance indicators—coulombic efficiency, energy efficiency, and capacity retention—are significantly inferior to the optimal system with added EDTA.

[0188] The various embodiments in this specification are described in a related manner. Similar or identical parts between embodiments can be referred to mutually. Each embodiment focuses on describing the differences from other embodiments. In particular, the system embodiments are basically similar to the method embodiments, so the description is relatively simple; relevant parts can be referred to the descriptions of the method embodiments.

[0189] The above description is merely a preferred embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention are included within the scope of protection of the present invention.

Claims

1. A method for preparing an aqueous organic iron-based flow battery, characterized in that, Includes the following steps: S1. A neutral salt solution is prepared using deionized water; the neutral salt solution is an aqueous solution of NaCl, NaBr, KCl, NH4Cl or NH4Br, with a molar concentration of 0.1~2M; S2. Soak and wash the anion exchange membrane in deionized water for 3-5 minutes to obtain a pretreated membrane. S3. The pretreated diaphragm is immersed in the neutral salt solution in S1 for ionization treatment, and the ionization treatment time is 1~48h. S4. Clean the ionized membrane and then soak it in deionized water for later use. S5. Ferrous sulfate and o-phenanthroline are dissolved in the neutral salt solution and stirred to obtain a positive electrode active material containing ferrous-o-phenanthroline complex; S6. EDTA is chelated with the positive electrode active material to prepare a positive electrode electrolyte. S7. Dissolve viologen derivatives in a neutral salt solution, stir to dissolve, and then perform deoxygenation treatment to obtain a negative electrode electrolyte. S8. Using graphite felt or carbon felt as electrode materials, the cleaned separator, positive electrolyte, and negative electrolyte are assembled to obtain an aqueous organic iron-based redox flow battery.

2. The method for preparing an aqueous organic iron-based flow battery according to claim 1, characterized in that, In step S4, the ionized membrane is washed 4 to 6 times with deionized water and then soaked in deionized water for later use.

3. The method for preparing an aqueous organic iron-based flow battery according to claim 1, characterized in that, In step S5, the molar concentration of the ferrous-o-phenanthroline complex is 0.1~0.5M, and the stirring time is 2h.

4. The method for preparing an aqueous organic iron-based flow battery according to claim 1, characterized in that, In step S6, the molar ratio of EDTA to o-phenanthroline is 1:1 to 1:

3.

5. The method for preparing an aqueous organic iron-based flow battery according to claim 1, characterized in that, In step S7, the viologen derivative is any one of MV, Dex-Vi, [(Me)(NPr)V]Cl3, [(NPr)2V]Br4, [(NPr)2TTz]Cl4, [(NPr)2PV]·4Cl, and [PyrPV]Cl4, with a molar concentration of 0.1~1M; The neutral salt solution used to prepare the negative electrode electrolyte has the same concentration as the neutral salt solution used to prepare the positive electrode electrolyte. The deoxygenation treatment is performed by introducing argon gas into a glove box for 40-50 minutes.

6. The method for preparing an aqueous organic iron-based flow battery according to claim 1, characterized in that, In step S8, the thickness of the graphite felt or carbon felt is 3~8mm.

7. An aqueous organic iron-based flow battery, characterized in that, The aqueous organic iron-based flow battery was prepared using any one of claims 1-6.